Formação de competências em saúde da criança nas residências de medicina de família e comunidade no Ceará. - Vasconcelos, Izabella Tamira Galdino Farias (2024)
This study aims to analyze the planning of competency development in child health within the pedagogical proposals of Family and Community Medicine Residency Programs in Ceará, focusing on Course Pedagogical Projects. The research is grounded in the general and specific competencies required by the guidelines of the National Medical Residency Commission and the Brazilian Society of Family and Community Medicine. Using a qualitative epistemological approach, exploratory and descriptive research was conducted based on documentary analysis. Using a proprietary data collection instrument, the pedagogical projects of seven Family and Community Medicine Residency Programs, responsible for ten training centers located in the state of Ceará, were analyzed from April to November 2024. The analysis was conducted under the perspective of Celso Vasconcellos and current regulations, focusing on competencies, content, workloads, teaching methodologies, and assessment strategies related to teaching and learning for promoting child health. The research adhered to ethical criteria, preserving the identity of the participating institutions. The results revealed varied designs of Course Pedagogical Projects, with evidence of both advancements and gaps in the development of child health competencies when analyzed through the lens of national normative guidelines and pedagogical practices significant for competency development. It was found that some programs offer robust proposals, while others lack detailed teaching-learning processes related to pediatric knowledge. The case analysis of the Pedagogical Project from the Family and Community Medicine Residency Program of the Visconde de Saboia School of Public Health in Sobral highlighted a robust Pedagogical Project that stands out positively among the others, showcasing best practices aligned with essential competencies, yet also pointing to areas for improvement. Finally, the study emphasizes the importance of greater integration between national guidelines and local curricula, as well as the need for investments in structuring the Pedagogical Projects of Family and Community Medicine Residency Programs in Ceará to enhance the development of child health competencies among residents. The study provides a foundation for reflections on the role of Family and Community Medicine Residency Programs in training physicians to deliver comprehensive care to the pediatric population in Primary Health Care. Additionally, it presents a guiding framework for developing Course Pedagogical Projects tailored to Family and Community Medicine Residency Programs.